Women’s problems in workplace of Bangladesh: an analytical study - Hossen, Belayet; Elatrash, Radwan Jamal Yousef; Osmani, Noor Mohammad (2018)
Bangladesh is one of the fastest growing countries in South Asia whose growth rate was 7. 1 percent and 7.2 percent in 2016 and 2017 respective years. In 2017 it was the second fastest growing country in South Asia. Behind this rapid growth of this country there is a great dedication of a big number of working women who came from rural areas of Bangladesh who have been working in different garment and textile industries across the country. In total 6500 factories the number of laborers is 4 million where 85% are women. However, this sector is playing very significant role to advance Bangladesh to the current position. The study found that the involvement of women in workplace indeed, is a sign of cooperation, rapid progress and prosperity for a developing country like Bangladesh. So, the owners of companies and governmental agencies should come forward to provide a peaceful and harassment-free atmosphere removing all sorts of obstacles for women to keep active the economic wheel of Bangladesh through ensuring necessary privileges which can encourage them to more massively contribute to the development of Bangladesh.